2016
DOI: 10.1097/igc.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care and Outcome of Elderly Women Diagnosed With Cervical Cancer in the Developing World

Abstract: Scarce data exist about the impact of age in cervical cancer (CC) patients in the developing world. The objective of the current study was to examine the patterns of care and outcome of elderly patients treated in a developing country. Medical records of patients treated from 2006-2009 at the Brazilian National Cancer Institute were reviewed. Patients were divided between women 70 years or older and women younger than 70 years. The χ tests were used and odds ratios were calculated. Survival was examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
(9 reference statements)
0
23
0
Order By: Relevance
“…However, in analysing patients who were younger or older than 70 years of age, the authors observed the following relationship: elderly patients have more advanced disease at the time of diagnosis, and this is the factor most indicative of a poorer prognosis. On the other hand, age is an important factor in the allocation of treatment, which also influences overall survival [3]. The classification of the patient for adequate radical therapy is crucial for improving survival.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in analysing patients who were younger or older than 70 years of age, the authors observed the following relationship: elderly patients have more advanced disease at the time of diagnosis, and this is the factor most indicative of a poorer prognosis. On the other hand, age is an important factor in the allocation of treatment, which also influences overall survival [3]. The classification of the patient for adequate radical therapy is crucial for improving survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nogueira-Rodrigues et al presented the results of treatment for a large group of patients, including 1339 younger patients and 143 elderly patients, treated for cervical cancer. The overall five-year survival rate among the younger patients was 58.2%, and 48.5% among the older patients (including all stages from FIGO I to IV) [3]. Nevertheless, most of our patients are diagnosed as LACC.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations